KATALOG GUGUS GALAKSI DENGAN 0.05 < Z < 0.30 DARI DATA SDSS DR5 - M. SIMATUPANG, FERRY
Study of galaxy clustering can give us information about history and evolution of galaxies, and large scale structure. Hence, identification of membership in a cluster is an important job. There is a handful of algorithms developed to identify cluster membership, either from observation or N-Body simulation. One of them is HOP, which is relatively new, developed by Eisenstein Hut (1998). HOP needs to be tested. In this work, HOP is applied to SDSS Data Release 5. With criteria: redshift 0.05 < z < 0.30 and confidence level in redshift zconf > 95%. HOP is used to build a catalog of galaxy cluster from SDSS DR5. Total galaxies involved are 382616 galaxies. The result is a catalog with 368 entries. The catalog is then compared to similar catalog from Miller et al. with SDSS DR2.